Health properties of oca (Oxalis tuberosa) and yacon (Smallanthus sonchifolius) - Jimenez, María Eugenia (2015)
Andean roots and tubers are underexploited crops; many contain compounds beneficial to health, so a greater knowledge of their properties is important for encouraging their consumption. The aim of this work was to study the content of bioactive compounds of yacon and oca and their effect on intestinal health using as a model rats of the Wistar strain. Two varieties of ocas (Overa and Rosada) and yacon, which contain significant amounts of fructooligosaccharides and phenolic compounds, were chosen. Rats of the Wistar strain were fed for two months with diets containing these foods in amounts sufficient to provide 8% of fiber. A significant decrease in pH values and an increment in lactobacilli and bifidobacteria counts in the cecum of rats fed with inulin, oca Rosada and Overa were observed; there was no significant decrease in enterobacteriaceae and enterococci counts. The cecum antioxidant activity was incremented in rats fed with the experimental foods with respect to the control diets. The components of dietary fiber and phenolic compound contents in yacon and oca produce effects that contribute to the intestinal health of the experimental animals.